Exploration of the factors that influence the implementation of environmental management systems: The case of Slovakia - Eva Petrová; Tomáš Štofa; Michal Šoltés (Economies, 2021)
Considering internationally accepted voluntary standards of an environmental management system (EMS) as tools that can help businesses meet the agenda for sustainable development and environmental wellbeing, this study aims to examine selected firm characteristics and financial performance that are potentially related to decisions of business entities in the matter of voluntary EMS implementation. We conduct empirical research based on logistic regression to study Slovak firms that are or are not certified according to ISO 14001 and EMAS standards. Our results suggest that there are several factors potentially determining the positive company choice to adopt voluntary EMS. We have confirmed the positive effect of firm size and research and development, however, we were not able to confirm the effects of foreign ownership and profitability effects. In the case of indebtedness, we have found a stronger negative effect of long-term debt. Our results also suggest a positive effect of owning a website, where companies can share information about their certificates. On the other side, especially younger companies tend to be interested in voluntary EMS.
Keywords: 330; business management; EMAS; ISO 14001; voluntary EMS